PENGARUH KNOWLEDGE MANAGEMENT DAN BUDAYA ORGANISASI MELALUI EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI MILENIAL PADA PUSDIKAT BADAN PUSAT STATISTIK JAKARTA - Junita Monica Angeline H (2022)
This research is a quantitative study with the aim of knowing whether there is an effect of knowledge management and organizational culture through employee engagement as a mediating variable on millennial employee performance. The objects in this study are millennial employees at the Jakarta Center for Statistics Education and Training Center. The data in the study came from the results of distributing questionnaires with the Google form to 31 respondents. Descriptive analysis and inferential analysis were carried out in this study. Testing in this study was assisted by SMARTPLS 4.0 software. Tests carried out are validity test, reliability test, test the coefficient of determination and test the hypothesis of direct and indirect influence. The research results obtained were: 1) knowledge management has a positive and significant effect on millennial employee performance, 2) organizational culture has a positive and significant effect on millennial employee performance, 3) employee engagement has a positive and significant effect on millennial employee performance, 4) knowledge management affects the performance of millennial employees through employee engagement, 5) organizational culture does not affect the performance of millennial employees through employee engagement.